2022
DOI: 10.1177/08862605221093684
|View full text |Cite
|
Sign up to set email alerts
|

Association of Child Sexual Abuse Victimization and Murderous Behaviors and the Mediating Role of Psychological Adjustment among College Students in China

Abstract: A history of child sexual abuse (CSA) is associated with a variety of psychological issues and conduct disorders in adolescents. However, little is known about the association between CSA and its characteristics and murderous behaviors in young adults. The purpose of this study was to examine this relationship and explore the mediating effect of psychological adjustment (PA). A cross-sectional study was conducted with 4034 college students in Anhui Province, China. The participants were invited to complete sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Cavaiola and Schiff (1988) reported that nearly 74% of adolescents who had suffered physical abuse and nearly 59% of adolescents who had suffered sexual abuse experienced homicidal ideation. Similarly, we previously demonstrated that child sexual abuse victimization was associated with an increased risk for murderous ideation and behaviors in college students (Li et al, 2023). Furthermore, a recent network analysis found that early adolescents who had experienced bullying in elementary school were more likely to report homicidal ideation than those who had not (Yuan et al, 2022).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Cavaiola and Schiff (1988) reported that nearly 74% of adolescents who had suffered physical abuse and nearly 59% of adolescents who had suffered sexual abuse experienced homicidal ideation. Similarly, we previously demonstrated that child sexual abuse victimization was associated with an increased risk for murderous ideation and behaviors in college students (Li et al, 2023). Furthermore, a recent network analysis found that early adolescents who had experienced bullying in elementary school were more likely to report homicidal ideation than those who had not (Yuan et al, 2022).…”
Section: Introductionmentioning
confidence: 55%
“…The risk factors for adolescent homicide ideation were shown to be complex and included psychological and social factors; several studies reported that homicide ideation was related to mental health problems, alcohol abuse and conduct disorders (Hohl et al, 2017; Vaughn et al, 2020; Waesche et al, 2016). In particular, increasing evidence demonstrated a strong link between CM and an elevated risk of homicidal ideation (Li et al, 2023; Su et al, 2018; Zhang et al, 2019). CM was a major global public health problem, and it included any form of abuse and neglect of children by parents and caregivers (Stoltenborgh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer victimization. Peer victimization was assessed using the Adolescent Peer Victimization Questionnaire (Li et al, 2015). This questionnaire was adapted from previously validated instruments (e.g., Olweus, 1993) to ensure its cultural, linguistic, and age appropriateness.…”
Section: Methodsmentioning
confidence: 99%
“…The theories that explain aggressive behaviors encompass cognitive associationism theory, social learning theory, social interaction theory, script theory, excitation transfer theory, the general affective aggression model, and ecological systems theory (Li et al, 2015;Zhi & Liu, 2003). Among them, ecological systems theory holds that every system in the social environment and its interactions have an effect on children's problem behaviors, and family and peers are important subsystems affecting aggressive behaviors (Li et al, 2015;Zhi & Liu, 2003).…”
Section: Th Eory a N D H Y Poth E Se S Theoretical Foundationmentioning
confidence: 99%